2003
DOI: 10.1001/archotol.129.7.716
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Lymphatics and Lymph Node Metastases in Papillary Thyroid Carcinoma

Abstract: The development of intratumoral lymphatics in well-differentiated papillary thyroid carcinoma appears to be associated with the spread of tumor to regional lymph nodes. The antimetastatic potential of targeting these lymphatics may be of potential therapeutic benefit in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
71
3
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 25 publications
12
71
3
5
Order By: Relevance
“…All of the stained vessels were typically thin-walled and devoid of red blood cells. Consistent with previous reports, 22 most lymph vessels were detected in carcinomas with an invasive margin (Figure 1c), and a few of these vessels were identified within the body of the carcinomas (data not shown). Mean intratumoral lymph vessel density was 4.6/each case, and mean peritumoral lymph vessel density was 13.6/each case.…”
Section: Immunohistochemistrysupporting
confidence: 93%
See 1 more Smart Citation
“…All of the stained vessels were typically thin-walled and devoid of red blood cells. Consistent with previous reports, 22 most lymph vessels were detected in carcinomas with an invasive margin (Figure 1c), and a few of these vessels were identified within the body of the carcinomas (data not shown). Mean intratumoral lymph vessel density was 4.6/each case, and mean peritumoral lymph vessel density was 13.6/each case.…”
Section: Immunohistochemistrysupporting
confidence: 93%
“…7 An earlier report using human papillary thyroid carcinoma also supported our present observation that the presence of lymphatics in papillary thyroid carcinoma was significantly associated with nodal metastasis. 22 VEGF-D expression is upregulated in a number of other types of tumors. 8,15 In this study, we found that increased VEGF-D expression was correlated with lymph node metastasis in papillary thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…9 Conversely, other investigators have suggested that lymphangiogenesis (formation of new tumorassociated lymphatics) plays an active role in the metastatic spread. [10][11][12] Previous studies have shown the potential clinical significance of intratumoral lymphatic microvessel density as a prognostic marker, correlating with the extent of tumor spread to regional lymph nodes, 11,13 although others have not demonstrated similar findings. 10,14,15 Previous studies have been limited by the lack of specific lymphatic endothelial markers that could be used to discriminate between lymphatics and blood vessels.…”
mentioning
confidence: 99%
“…There has been debate in the literature as to whether lymphatic vessels exist within tumours (Leu et al, 2000;Nathanson et al, 2000;Padera et al, 2000;Birner et al, 2001;Mandriota et al, 2001;Schoppmann et al, 2001;Skobe et al, 2001;Stacker et al, 2001;Beasley et al, 2002;Dadras et al, 2003;Hall et al, 2003;Maula et al, 2003;Straume et al, 2003;Williams et al, 2003); whether tumours induce lymphangiogenesis (Leu et al, 2000;Nathanson et al, 2000;Sleeman, 2000;Mandriota et al, 2001;Schoppmann et al, 2001;Skobe et al, 2001;Stacker et al, 2001;Beasley et al, 2002;Williams et al, 2003); whether lymphangiogenesis or dilated pre-existing lymphatic vessels increase the probability of lymphatic tumour dissemination (Leu et al, 2000;Padera et al, 2000;Sleeman, 2000;Dadras et al, 2003;Straume et al, 2003;Bono et al, 2004); and whether cancer cells require active intravasation (Hartveit, 1990;Gunningham et al, 2000;Kinoshita et al, 2001;Schoppmann et al, 2001).…”
mentioning
confidence: 99%